8 Documents and Records Relating to the State of New Hampshire During the Period of the American Revolution from 1776-1783, at 15-16 (Nathaniel Bouton ed., 1874) - (:unkn) unknown (My University, 1775)
Requiring each firearm sold in the colony to possess certain specifications and pass inspection involving the safe firing of the gun.
Keywords: MANUFACTURE ONLY